PENGARUH PERMAINAN WORD CARD TERHADAP KEMAMPUAN MENYUSUN KALIMAT DAN PENGGUNAAN TANDA BACA PADA SISWA DI MADRASAH IBTIDAIYAH - Lola Lailatul Fitri; Rizqiyah Ratu Balqis (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the extent to which the learning method using the Work Card game influences the reading and writing literacy skills of third-grade students at MI Assuniyah 45 Paseban. The method used in this study is a direct method applied by researchers in the classroom (experimental) for two months. The participants of this study consisted of 22 third-grade students at MI Assuniyah 45 Paseban. The date of the study was September 15, 2025. The data collection method used a pre-experiment with a one-group design, with pre-tests and post-tests. The study showed that students' ability to construct sentences and use punctuation improved after the Word Card game was implemented. Based on the results of the normality test, the research data were normally distributed, thus meeting the requirements for hypothesis testing. Furthermore, the results of the paired t-test showed a significance value of 0.000 (p < 0.05) for both sentence construction and punctuation skills. This indicates a significant difference between the initial and final exam scores. Thus, it can be concluded that the Word Card game has a significant impact on the ability of third-grade students of MI Assuniyah 45 Paseban to construct sentences and use correct punctuation. The Word Card game can be used as an alternative way to learn Indonesian, thereby helping to improve elementary school students' reading and writing skills.